2020
DOI: 10.1088/1361-648x/ab6021
|View full text |Cite
|
Sign up to set email alerts
|

Majorana corner modes in an s-wave second order topological superfluid

Abstract: We propose a method to prepare Majorana pairs at the corners of imprinted defects on a twodimensional cold atom optical lattice with s-wave superfluid pairing. Different from previous proposals that manipulate the effective Dirac masses, our scheme relies on the sign flip of the spin-orbit coupling at the corners, which can be tuned in experiments by adjusting the angle of incident Raman lasers. The Majorana corner pairs are found to be located at the interface between two regimes with opposite spin orbit coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…It is found that the cooperation of the OIPZE and s-wave pairing order could also leads to Dirac mass possessing opposite signs at adjacent edges. However, contrary to the in-plane Zeeman field in references [84,85], OIPZE determines the sign of Dirac mass along y while not along x.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…It is found that the cooperation of the OIPZE and s-wave pairing order could also leads to Dirac mass possessing opposite signs at adjacent edges. However, contrary to the in-plane Zeeman field in references [84,85], OIPZE determines the sign of Dirac mass along y while not along x.…”
Section: Introductionmentioning
confidence: 69%
“…The topological classification of HOT states has been made based on spatial symmetries [82,83]. Recently, to avoid complex pairings and complicated lattice structures, it is proposed that secondorder topological SCs and SFs could emerge in a quantum spin-Hall insulator with the s-wave pairing and the in-plane Zeeman field [84,85]. In these schemes, the in-plane Zeeman field as a key parameter gives rise to the opposite Dirac masses on adjacent edges, and induces Majorana zero-energy states at corners.…”
Section: Introductionmentioning
confidence: 99%
“…Topological systems are of great significance in the condensed-matter physics. [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] The researches on non-Hermitian Su-Schrieffer-Heeger (SSH) chain, Chern insulator, and nodal-line semimetals have received great interests. [67][68][69][70][71][72][73][74][75] As the progress on optical realization of the topological systems, the field of topological photonics has been stimulated.…”
Section: Introductionmentioning
confidence: 99%
“…The topological classification of HOT states has been made based on spatial symmetries [75,76]. Recently, to avoid complex pairings and complicated lattice structures, it is proposed that secondorder topological SCs and SFs could emerge in a quantum spin-Hall insulator with the s-wave pairing and in-plane Zeeman field [77,78]. In these schemes, the in-plane Zeeman field gives rise to the opposite Dirac masses on adjacent edges, and induces Majorana zero-energy states at corners.…”
Section: Introductionmentioning
confidence: 99%
“…However, contrary to the inplane Zeeman field in Refs. [77,78], OIPZE determines the sign of Dirac mass along y while not along x.…”
Section: Introductionmentioning
confidence: 99%